Manajemen Pendidikan Karakter Pada Sekolah Dasar Islam Kurikulum Terpadu (SDIKT) Robbi Rodhiya di Kota Bandar Lampung - Udhhiyah, Lailatul; Kholid, Idham; Yetri, Yetri (El-Idare, 2023)
This research discusses character education management at the Integrated Curriculum Islamic Elementary School (SDIKT) Robbi Rodhiya in Bandar Lampung City. Character education is an essential part of the educational process to shape a generation with noble morals and ethics. This study aims to evaluate the planning, organization, implementation, and supervision of character education at SDIKT Robbi Rodhiya. The research method used is qualitative research with data collection through interviews, observations, and document analysis. The results of the study show that character education management at SDIKT Robbi Rodhiya prioritizes the role of teachers in instilling character values in students. The character education process involves various aspects, including curriculum, training, and mentoring. Character education planning at this school has been well integrated into the curriculum, while character education organization involves all school components. The implementation of character education includes various activities such as scouting, religious studies, and sports. Character education supervision is carried out through monitoring by teachers and the school community. The results of this research can serve as a reference for other schools in developing effective and sustainable character education management.